Pediatric penile biometry guides the surgical outcome following tubularised incised plate urethroplasty for hypospadias: a single centre study - Das, Debjani; Ghosh, Arindam; Sinhababu, Aloke Kumar; Pal, Sujay; Patra, Rishavdeb; Sasmal, Debojyoti (International Journal of Contemporary Pediatrics, 2023)
Background: In hypospadias urethral meatus opens onto the ventral surface of the penis proximal to tip of glans and its surgery is challenging. Recent focus of hypospadias surgery is on reduction of postoperative complications and objective assessment of penile anthropometry which can affect outcome. Aim of study was to assess the surgical outcome of tubularised incised plate urethroplasty on penile biometric parameters among children with coronal, distal penile and mid penile hypospadias. Methods: Study was conducted in the department of pediatric surgery in IPGMER and SSKM Hospital in Kolkata during November 2019 to October 2021. Results: Among 42 boys mean urethral plate length is 4.286 (coronal), 7.643 (distal penile) and 8.846 (mid penile), mean urethral plate width is 3.321 (coronal), 5.786 (distal penile) and 5.923 (mid penile), mean diameter at mid glans level is 4 (coronal), 5.071 (distal penile) and 5.923 (mid penile), mean diameter at coronal level is 5.75 (coronal), 6.429 (distal penile) and 6.769 (mid penile), mean stretched penile length is 39.2143 (coronal), 41.857 (distal penile) and 40.308 (mid penile) hypospadias respectively. P value is less than 0.05 for all except urethral plate depth which has a non-significant p value. Conclusions: Urethral plate length, urethral plate width, mid glans diameter, glans diameter at coronal sulcus level and stretched penile length affect the outcome of the surgical process TIP urethroplasty in coronal, distal penile and mid penile type hypospadias but urethral plate depth does not.